A micrometer-sized europium(iii)–organic framework for selective sensing of the Cr2O72− anion and picric acid in water systems. Issue 39 (27th September 2017) - He, Hongming; Chen, Si-Hang; Zhang, De-Yu; Hao, Rui; Zhang, Chao; Yang, En-Cui; Zhao, Xiao-Jun
Abstract : A micrometer-sized europium(iii )–organic framework with good dispersibility, excellent thermal and environmental stability, and easy regeneration ability can serve as a dual-responsive luminescent sensor to probe both Cr2 O7 2− and picric acid contaminants in water system. Abstract : A micrometer-sized europium(iii )–organic framework with asymmetric binuclear metal subunits extended by 4, 5-dichlorophthalaten (DCPA), [Eu2 (H2 O)(DCPA)3 ] n, was easily obtained using a reverse microemulsion method. The framework exhibits good dispersibility, excellent thermal and environmental stability and easy regeneration ability. More importantly, the complex displays strong red emission and can selectively and sensitively detect both inorganic Cr2 O7 2− anions ( K sv = 8.7 × 10 3 M −1 ) and organic picric acid contaminants ( K sv = 1.07 × 10 4 M −1 ) in water systems through fluorescence quenching. A luminescent film of1 was further prepared and successfully used to detect the Cr2 O7 2− anion in an aqueous system. These interesting results indicate that the well-dispersed europium(iii )–organic framework can serve as a promising dual-responsive luminescent sensor for environmental pollutant monitoring.